COBRA Master Class: Providing deep-sea expedition leadership training to accelerate early career advancement - Rotjan, Randi D.; Bell, Katherine L. C.; Huber, Julie A.; Wheat, Charles Geoffrey; Fisher, Andrew T.; Sylvan, Rosalynn Lee; McManus, James; Bigham, Katharine T.; Cambronero-Solano, Sergio; Cordier, Tristan; Goode, Savannah; Leonard, Juliana; et al. (Frontiers in Marine Science, 2023)
Leading deep-sea research expeditions requires broad training and experience, and the opportunities for Early Career Researchers (ECRs) to obtain focused mentorship are scarce. To address this need, the Crustal Ocean Biosphere Research Accelerator (COBRA) launched a 14-week virtual Master Class to empower students with the skills and tools to successfully design, propose, and execute deep-sea oceanographic field research. The Master Class offered training and created an open-access syllabus with resources, including reading material, lectures, and online resources freely-available online (cobra.pubpub.org). All COBRA Fellows were ECRs, and engaged in topics related to choosing deep-sea research assets, learning about funding and how to tailor proposals, and working through an essential checklist of pre-expedition planning and operations. The Master Class covered leading an expedition at sea, at-sea operations, and ship-board etiquette, and telepresence. It also included post-expedition training on data management and report preparation. Fellows also discussed education and outreach, international ocean law and policy, and team science. Fellows further learned about how to develop concepts respectfully with regard to geographic and cultural considerations of their intended study sites. An assessment of initial outcomes from the first iteration of the COBRA Master Class reinforces the need for such training and shows great promise with one-quarter of the Fellows having submitted a research proposal to national funding agencies within six months post-class. As deep-sea research continues to accelerate in scope and speed, providing equitable access to expedition training is a top priority to enable the next generation of deep-sea science leadership.